Validation of an Instrument and Measurement of Employee Work-Life Policies, Psychological Empowerment, and Job Commitment of Academic Staff in Universities - Owan, Valentine Joseph; Bassey, Bassey Asuquo; Mbon, Usen Friday; Okon, Abigail Edem; Egbula, Ene Ogar; Ekaette, Samuel Okpon; Ojong, Cyprian Oba; Ekpe, Mercy Bassey (Mediterranean Journal of Social Sciences, 2020)
This study used a structural equation modelling approach to assess the association between employee work-life policies, psychological empowerment, and academic staff job commitment in universities in Cross River State, Nigeria. Three null hypotheses were formulated to guide the study following a descriptive survey research design. Multistage sampling procedure was adopted in the selection of 315 academic staff from two universities in the study area. â€œWork-Life Policies, Psychological Empowerment and Job Commitment Questionnaire (WPPEJCQ)â€ was used as the instrument for data collection. The construct validity of the instrument was ascertained through an Exploratory Factor Analysis (EFA) using the Principal Component Analysis (PCA). The Kaiser-Meyer-Ohlin of .894 and the Bartlett coefficient of 7795.820 were obtained. Several fit indices of Confirmatory Factor Analysis were used to accept the model such as RMSEA=.031, TLI=.969, CFI=.971 and many others. The null hypotheses were all tested using Path analysis. Findings revealed, among others, that there is a significant effect of work-life policies on the affective (Î²=.774,t=21.636,p<.05), continuance (Î²=.450,t=8.932,p<.05), and normative (Î²=490,t=9.967,p<.05) dimensions of academic staff commitment; furthermore, psychological empowerment has a significant effect on the affective (Î²=.795,t=23.199,p<.05), continuance (Î²=.501,t=10.261,p<.05) and normative (Î² = .520, t = 10.795, p< .05) dimensions of staff commitment; and there is a significant composite effect of work-life policies and psychological empowerment on the affective, continuance, and normative commitment levels of academic staff in universities. Based on these findings, conclusions and recommendations were made